Disaster-induced migration types and patterns, drivers, and impact: A union-level study in Bangladesh. (2022) - Chumky, Tahmina; Basu, Mrittika; Onitsuka, Kenichiro; Parvin, Gulsan Ara; Hoshino, Satoshi
Highlights: Union-level study is conducted to investigate disaster-induced migration in Bangladesh. Migration is mainly practiced as an alternative livelihood strategy. Major spatial and temporal migration patterns are temporary migration from rural to urban areas. Auxiliary drivers including economic drivers exacerbate migration in the aftermath of a disaster. Migration is perceived to improve the family income of the migrant. Abstract: Environmental shocks like disasters are reported to induce migration in different parts of the world. Bangladesh has been witnessing migration across the years, but the underlying mechanism of disaster-induced migration needs to be explored and understood with changing climate conditions. The main objective of this study is to evaluate disaster-induced migration types and patterns, the auxiliary drivers and the perceived impact of migration. A semi-structured questionnaire survey was carried out with 155 Union-level key persons from five districts of Bangladesh, and collected qualitative data were thematically analyzed using NVivo. Irrespective of the type of disaster, the major spatial-temporal pattern of migration was perceived to be temporary domestic migration from rural to urban areas. Comparing the auxiliary drivers of migration revealed some common economic drivers. The comparison diagram also identifies several other drivers which are disaster-specific. For e.g., social, demographic, and physical drivers are perceived to drive migration in cyclone-affected areas, while environmental drivers (land degradation, scarcity of safe drinking water, changes in soil condition, etc.) are the primary drivers behind migration in saline-affected areas. Regarding impacts, though household economic status is perceived to get better post-migration, loss of traditions and cultural value, loss of social ties, and loss of security are identified as some of the negative impacts of disaster-induced migration. The current study emphasizes that a migration policy as an umbrella policy may mask the local challenges and community requirements and argues for the need of a disaster-specific migration policy that addresses disaster-induced challenges encountered by local communities.